The relationship between employment policies, employment levels and local development in South Africa : a case of Polokwane Local Municipality in Limpopo Province, South Africa - Mashabela, Chungu Mamahlodi (My University, 2025)
The study investigated the relationship between employment policies, employment levels, and local development in South Africa, using the Polokwane municipal area as its case study. The objectives of the study were to analyse the employment legislative framework and its influence on employment growth in South Africa; examine the relationship between employment policies and employment levels in South Africa; examine the impact of employment policies on local development in Polokwane Local Municipality; analyse the impact of employment levels on local development in Polokwane Local Municipality and to develop a local development model that has the potential to increase employment levels and enhance local development in South Africa. The study adopted a mixed-methods research design, integrating both qualitative and quantitative approaches. Data were collected through structured interviews and questionnaires, with sampling conducted using both probability and non-probability techniques. Data analysis was performed using Microsoft Excel 2010 for quantitative data and thematic analysis for qualitative responses. The study found that employment policies influence employment growth. While some regulations aim to protect workers' rights and promote fair labour practices, overly rigid regulations can sometimes discourage hiring and increase labour costs, potentially leading to lower employment levels. Conversely, flexible regulatory frameworks enable businesses to adapt more efficiently to market fluctuations, potentially stimulating job creation. Additionally, the study identified challenges in policy compliance among employers, as well as enforcement difficulties faced by the Department of Labour. These compliance and enforcement gaps undermine the effectiveness of employment policies, limiting their potential to drive meaningful employment growth. Furthermore, the findings indicate that both employment policies and employment levels exert considerable influence on local development. On one hand, well-structured employment policies foster an inclusive labour market, enabling broader workforce participation. On the other hand, persistently high unemployment exacerbates socio-economic disparities, increasing reliance on government welfare programmes. This dependency reduces municipal revenue streams, constraining service delivery and impeding local development. To address these challenges, the study recommends regulatory streamlining and simplifying complex labour regulations, which could enhance compliance and reduce administrative burdens on businesses. This can make it easier for companies to navigate the legal landscape and focus on creating jobs. Additionally, the study recommends investment in skills development, bridging the skills gap through targeted education and vocational training programmes, which is critical to improve workforce employability. Moreover, the study recommends supporting small and medium-sized enterprises and fostering an entrepreneurship culture. SMMEs are significant job creators in many economies. Assisting SMMEs by providing access to financial resources, business development services and streamlined regulations can help them grow and create more jobs. This can significantly improve employment levels and ultimately enhance local development in South Africa. The study underscores the pivotal role of employment policies and employment levels in shaping local development outcomes. Higher employment rates correlate with increased household incomes, greater local expenditure, and strengthened municipal revenue bases, which contribute to sustainable economic growth. By implementing the proposed recommendations, policymakers can foster a more dynamic labour market, ultimately advancing both employment and local development in South Africa.
Thesis (Ph. D. (Public Administration)) -- University of Limpopo, 2025
Keywords: Employment policies; Employment levels; Local Development; South Africa; Full employment policies -- South Africa; Unemployment -- South Africa; Community development -- South Africa -- Limpopo; Manpower policy -- South Africa -- Limpopo; Labor